LOWEST POSSIBLE FELLING TECHNIQUE FOR INCREASING UTILIZATION OF RENGHAS (Gluta renghas L.) WOOD AT A PEAT SWAMP FOREST - Sona Suhartana; Yuniawati Yuniawati (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2006)
This study was carried out in 2005 at a peat swamp forest company in Jambi. The aim of this study was to find out a technique to increase the utilization of renghas wood in a peat swamp forest by implementing the lowest possible felling technique (LPFT) and the conventional felling technique (CFT). Data collected in this study were: working time, log volume, waste volume, productivity, efficiency, stump height and felling cost. Two data categories were analyzed with respect to their possible differences by using a t-test.The study showed that the implementation of LPFT produced better results compared to that of CFT which was indicated by: (1) Felling productivity increased to 5.220 m3/hour, (2) Felling cost decreased Rp 341/m3, (3) Felling efficiency increased 3.2%, and (4) The average stump heights were 41.2 cm for LPFT and 67.5 cm for CFT.